The Effect of Academic Supervision and Teacher’s Motivation on Teacher’s Performance - Puri, Reni Dian; Ahmad, Syarwani; Wahidy, Achmad (Journal of Social Work and Science Education, 2023)
This research was conducted with the aim of clearly and straightforwardly describing the influence of academic supervision and teacher motivation on the achievement of teacher’s performance. Therefore, the method used in this research is descriptive quantitative so as to be able to provide a firm answer through hypothesis testing. The results obtained from the research that has been done that partially academic supervision is able to have a positive and significant influence on teacher’s performance, as well as teacher motivation who also participates in giving effect to work performance achievement. The tests carried out simultaneously stated that academic supervision and teacher motivation were able to have a positive and significant influence on teacher’s performance in State Vocational Schools throughout Muara Enim District, amounting to 36.8% and included in the sufficient category.